(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the relationship between the development of postpartum depression after obstetric violence. Methods: This is an integrative literature review, conducted by searching for scientific articles in the electronic databases National Library of Medicine of the National Institute of Health of the United States (PubMED), Online Scientific Electronic Library (SciELO), Latin American and Caribbean Literature on Health Sciences (LILACS), Cochrane Collaboration and the Google Scholar search tool, between 2012 and 2022. The descriptors used in the research are indexed in the Health Sciences Descriptors (DeCS) , being “Postpartum Depression” and “Obstetric Violence” and their English counterparts, “Depression, Postpartum” and “Obstetric Violence”, associated by the Boolean operator “AND”. A total of 136 articles were found; of these, 24 were selected following the inclusion criteria, submitted to qualitative analysis and discussed. Results and Discussion: Despite the protective rights against obstetric violence, many women suffer threats to their physical and psychological integrity, right to information and freedom of choice in the act of childbirth, predisposing them to the development of puerperal depression, either due to the precarious knowledge of the pregnant women about their rights and appropriate obstetric practices at the time of delivery to psychosocial determinants, such as education level, economic income and ethnicity. Conclusion: Therefore, it is necessary to disseminate information to pregnant women about their rights and what characterizes obstetric violence, so that they can take a stand when necessary, reducing the rates of childbirth-related trauma and, thus, puerperal depression.